Langston Hughes and American Lynching Culture - Miller, W. Jason (Book collections on Project MUSE., 2011)
Langston Hughes never knew of an America where lynching was absent from the cultural landscape. This study of the centrality of these heinous acts to Hughes' artistic development aesthetics, and activism represents a significant contribution to our understanding of the art and politics of Langston Hughes.